The impact of patient safety culture on handover in rural health facilities - Donella Piper; Jackie Lea; Cindy Woods; Vicki Parker (BMC, 2018)
Abstract Background Effective handover is crucial for patient safety. Rural health care organisations have particular challenges in relation to handover of information, placing them at higher risk of adverse events. Few studies have examined the relationship between handover and patient safety in rural contexts, particularly in Australia. This study aimed to explore the effect of handover on overall perceptions of patient safety and the effect of other patient safety dimensions on handover in a rural Australian setting. Methods A cross-sectional online survey using The Agency for Healthcare Research and Quality Hospital Survey on Patient Safety Culture was implemented across six rural Local Health Districts in NSW, Australia and resulted in 1587 respondents. Hierarchical multiple linear regression analysis was conducted to account for the nested nature of the data. Models were developed to assess the effect of handover on patient safety perceptions, and the effect of other patient safety culture composites on handover variables. Open-ended questions about patient safety were inductively analyzed for themes. Quotes from the handover theme are presented. Results All models were significant overall (p < .001), with explanatory powers ranging from 29 to 48%. Within rural health settings, effective handover is significantly related to patient safety perceptions (R 2  = .29). A strong teamwork culture and management support culture was found to enhance effective handover of patient information (R 2  = .47), and effective handover of personal responsibility (R 2  = .37). A strong teamwork, management support, and open communication culture enhances handover of department accountability (R 2  = .41). Despite the implementation of standardised communication tools and frameworks for handover, patient safety is compromised by inadequate coordination, poor or absent documentation between departments, between other health care agencies and in transfer of care from acute facilities to primary/community care. Conclusion Approaches to handover need to consider the particular challenges associated with rurality and strengthening elements found to be associated with increased safety, such as a strong teamwork and management culture and good reporting practices. Research is required to examine how communication at transition of care, particularly between facilities, is conducted and ways in which to enhance patients' and families' participation.